Early conversion to a CNI-free immunosuppression with SRL after renal transplantation-Long-term follow-up of a multicenter trial - Andrassy, Joachim; Guba, Markus; Habicht, Antje; Fischereder, Michael; Pratschke, Johann; Pascher, Andreas; Heller, Katharina M.; Banas, Bernhard; Hakenberg, Oliver; Vogel, Thomas; Meiser, Bruno; Dick, Andrea; et al. (PLoS ONE, 2020)
INTRODUCTION: Early conversion to a CNI-free immunosuppression with SRL was associated with an improved 1- and 3- yr renal function as compared with a CsA-based regimen in the SMART-Trial. Mixed results were reported on the occurrence of donor specific antibodies under mTOR-Is. Here, we present long-term results of the SMART-Trial. METHODS AND MATERIALS: N = 71 from 6 centers (n = 38 SRL and n = 33 CsA) of the original SMART-Trial (ITT n = 140) were enrolled in this observational, non-interventional extension study to collect retrospectively and prospectively follow-up data for the interval since baseline. Primary objective was the development of dnDSA. Blood samples were collected on average 8.7 years after transplantation. RESULTS: Development of dnDSA was not different (SRL 5/38, 13.2% vs. CsA 9/33, 27.3%; P = 0.097). GFR remained improved under SRL with 64.37 ml/min/1.73m2 vs. 53.19 ml/min/1.73m2 (p = 0.044). Patient survival did not differ between groups at 10 years. There was a trend towards a reduced graft failure rate (11.6% SRL vs. 23.9% CsA, p = 0.064) and less tumors under SRL (2.6% SRL vs. 15.2% CsA, p = 0.09). CONCLUSIONS: An early conversion to SRL did not result in an increased incidence of dnDSA nor increased long-term risk for the recipient. Transplant function remains improved with benefits for the graft survival.
CRIS-Team Scopus Importer:2020-08-14